Analysis of the Impact of Implementing Wireless Security Protocol (WPA2-PSK and WPA3-SAE) on Handover Performance on 5Ghz Network - Sofian Dwi Hadiwinata; Alva Hendi Muhammad; Ilham Setya Budi (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to analyze the impact of implementing wireless security protocols WPA2-PSK and WPA3-SAE on handover performance in 5 GHz networks. Efficient handover is crucial to maintaining seamless connectivity and quality of service in WiFi networks, especially on the 5 GHz frequency band widely used for high bandwidth applications. The research method involves testing and measuring handover performance parameters such as handover latency, connection handover success rate, and signal stability for both security protocols. The analysis results indicate that although WPA3-SAE offers significant security improvements compared to WPA2-PSK, there are differences in handover performance that need to be considered. WPA3-SAE tends to cause slightly higher handover latency due to its more complex authentication process but still provides good connection stability. Conversely, WPA2-PSK show lower handover latency but with a lower level of security. These findings provide important insights for network administrators in selecting a security protocol that balances security needs and handover performance to optimize user experience on 5 GHz networks.